2018
DOI: 10.1021/acsomega.8b01588
|View full text |Cite
|
Sign up to set email alerts
|

Convenient and Template-Free Route to One-Pot Green Synthesis of Polyrhodanine Core–Shell Nanoparticles

Abstract: In this publication, a copper acetate-mediated rhodanine polymerization reaction is examined. It is demonstrated that at room temperature, Cu(II) acetate complexes with rhodanine generate solid nanospheres, which, upon heating in a microwave, results in polyrhodanine core–shell nano- and microsphere particles. The structural analysis of the polyrhodanine nanosphere produced by this efficient microwave-initiated method was conducted by Fourier transform infrared spectroscopy, UV–vis spectroscopy, scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The key problem is to fabricate core–shell-encapsulated arrays for the quantitative release of diversiform odorous molecules. The capsules contain an aqueous core with odorous molecules and a PLGA protective shell .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The key problem is to fabricate core–shell-encapsulated arrays for the quantitative release of diversiform odorous molecules. The capsules contain an aqueous core with odorous molecules and a PLGA protective shell .…”
Section: Results and Discussionmentioning
confidence: 99%
“…An interesting study reported that utilisation of copper acetate as an oxidising agent in synthesis of PR nano-/microspheres. In this direct one-pot and green approach, its polymerisation happened under mild conditions, based on microwave synthetic protocol, as well as a green solvent involved in this transformation, such as water or ethanol [ 17 ]. The oxidative oligo-/polymerisation process was initiated and led to the formation of a complex of copper (Cu) with rhodamine.…”
Section: Synthesis Of Pr and Its Nanocompositesmentioning
confidence: 99%
“…Our interest in the area of phase transfer is need based. In our laboratory, we have developed new methodologies for one pot creation of novel metal nanoparticles in organic and aqueous solvents [ 66 , 67 , 68 , 69 ]. In our ongoing projects, we have water-soluble nanoparticles, which we want to tailor with drug molecules.…”
Section: Future Directionsmentioning
confidence: 99%